Climate risk co-movements effect on South Asia’s emerging stock market for financial inclusion - Waheed Ullah Shah; Ibtissem Missaoui; Ijaz Younis; Xiyu Liu (Future Business Journal)
Abstract Ecological risks and climate change have vulnerable effects on the financial markets. Using wavelet time–frequency analysis, our study explores the interim effect of climate flood-disaster risk co-movements on the South Asian emerging stock market for financial inclusion. We selected the vital stock indexes of the South Asian emerging (Pakistan) stock market during the recent climatic flood-disaster event in June 2022 using a wavelet time–frequency for climate risk co-movement analysis. The Morgan Stanley Capital International (MSCI) Pakistan stock pairs (MSCI-Global X Morgan Stanley Capital International Exchange Traded Fund (GXMSCI-ETF), MSCI-Karachi Meezan Index-30 (KMI), MSCI-Karachi stock exchange (KSE100) index, and pair MSCI-Karachi stock exchange all share (KSE) index risk co-movements significantly lead to higher- and lower-frequency zones during disaster events with coherence values exceeding (0.75) at significance level throughout the (01–105-days) period. Furthermore, all stock pairs are positive, leading to risk co-movements at higher- and lower-frequency zones except the pair MSCI-Frontier Markets Index Series (FTSE) and MSCI-GXMSCI-ETF index during full sample (1–359 days). MSCI-GXMSCI-ETF leads, while MSCI-FTSE lags but is insignificant despite coherence greater than (0.75). However, all selected indices have negative mean returns with KMI (− 0.020926) maximum and FTSE (− 0.179684) minimum values during flood-disaster events. The findings offer novel insights into how natural disasters influence stock market behavior, particularly in emerging economies in South Asia such as Pakistan.